Investigation of the effects of VGF overexpression and VGF-derived peptides on lipolysis in 3T3-L1 cells - Dean, Holly (2022)
Obesity is a common problem in the UK affecting 1 in 4 adults and 1 in 5 children, and the prevalence of obesity is steadily increasing. Obesity is becoming more widely recognised as hormonal dysregulation of fat accumulation rather than being solely attributed to caloric energy imbalance. The neuroendocrine pro-hormone VGF is processed into a variety of peptide hormones and has been linked to energy homeostasis and insulin secretion, with expression of VGF in human adipose tissue and plasma levels of VGF-derived peptides correlating negatively with obesity. It has been hypothesised that some VGF-derived peptides may exert opposing effects. The VGF-derived peptide TLQP-21 induces lipolysis in adipocytes, however, the effects of VGF and its derived peptides TLQP-62 and AQEE-30 on adipocyte lipid content in vitro have not yet been investigated. Here we show that treatment of 3T3-L1 adipocytes with TLQP-62 significantly increased cellular lipid content, whereas treatment with AQEE-30 and VGF overexpression had no significant effect on lipid content. We found that lipid-based transfection of 3T3-L1 pre-adipocytes was toxic and resulted in cell death, whereas transfection of partially differentiated 3T3-L1 adipocytes was inefficient and induced an insignificant reduction in lipid accumulation compared to adipocytes transfected with a control construct lacking vgf. Furthermore, we found that TLQP-62 and AQEE-30 had no significant effect on cellular lipid content when administered in the absence of isoproterenol. However, when administered with isoproterenol, TLQP-62 significantly increased 3T3-L1 lipid content and AQEE-30 significantly inhibited isoproterenol-induced lipolysis in 3T3-L1 adipocytes. Our results demonstrate that TLQP-62 may induce lipogenesis in 3T3-L1 cells via β-adrenergic signalling pathways and supports the hypothesis that some VGF-derived peptides may have opposing effects in energy homeostasis in vivo. We anticipate that VGF could provide targets for the treatment of obesity and T2DM, and a greater understanding of the relationships between VGF-derived peptides could be relevant for the development of new intervention strategies.